Site-specific differences in the association between plantar tactile perception and mobility function in older adults - Cruz-Almeida, Yenisel; Black, Mieniecia L.; Christou, Evangelos A.; Clark, David J. (Frontiers in Aging Neuroscience, 2014)
Introduction Impaired somatosensation is common in older adults and contributes to age-related loss of mobility function. However, little is known about whether somatosensation at different sites on the plantar surface of the foot are differentially related to mobility function. Such a finding may have important implications for clinical care of older adults and other at-risk populations, such as for optimizing interventions (e.g., footwear for augmenting somatosensory feedback) and for improving the efficiency of clinical assessment. Materials and Methods Tactile perception was evaluated with a 10g monofilament at four sites on the plantar surface of each foot: great toe (GT), first metatarsal head (MT1), heel (H) and fifth metatarsal head (MT5). Mobility function was assessed with the Berg Balance Scale and walking speed. Results Sixty-one older adults participated. Tactile perception was significantly positively associated with Berg Balance Score (adjusted R2 = 0.30 - 0.75; p = 0.03 - < 0.001), with the strongest association found at the site of the first metatarsal head (MT1). Only at this site was tactile perception found to be significantly associated with usual walking speed (adjusted R2 = 0.51; p < 0.001) and maximal walking speed (adjusted R2 = 0.38, p = 0.004). Clinically mild somatosensory impairment at MT1, but not at other sites, was found to yield substantial deficits in both Berg Balance Score and walking speed. Discussion The present findings indicate that tactile perception at MT1 is more closely linked to mobility function than is tactile perception at GT, MT5 or H. These findings warrant further research to examine whether interventions (e.g., textured insoles) and assessments that preferentially or exclusively focus on the site of MT1 may be more effective for optimizing clinical care.